1992
DOI: 10.1073/pnas.89.21.10006
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and functional immaturity of human umbilical cord blood T lymphocytes.

Abstract: Successful implementation of bone marrow transplantation for hematopoletic reconstitution is limited by the lack of suitably IELA-matched donors and by the occurrence of graft-versus-host disease that frequently accompanies this procedure. Recent clinical reports have implied that the use of umbilical cord blood as a source of transplantable stem cells may solve these problems. To date, definitive experiments have not been performed to assess the immunological potential of T cells found in umbilical cord blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
188
3
7

Year Published

1999
1999
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 315 publications
(214 citation statements)
references
References 18 publications
16
188
3
7
Order By: Relevance
“…; 570 ± 15.7) T cells. This observation is in contrast to that of Harris et al 41 who reported decreased density of CD3 on cord blood T cells. However, these investigators did not provide data on background staining with isotype control.…”
Section: Genes and Immunitycontrasting
confidence: 99%
See 4 more Smart Citations
“…; 570 ± 15.7) T cells. This observation is in contrast to that of Harris et al 41 who reported decreased density of CD3 on cord blood T cells. However, these investigators did not provide data on background staining with isotype control.…”
Section: Genes and Immunitycontrasting
confidence: 99%
“…18,31,32,41 Therefore, decreased TNFR-I expression in cord blood T cells could be due to a shift towards CD45RA + population. However, we observed no significant difference in the expression of TNFR-I in CD45RA + and CD45RO + subsets of CD4 + and CD45RA + subsets of CD8 + T cells between cord blood and peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations